2016
DOI: 10.1007/s12192-015-0634-8
|View full text |Cite
|
Sign up to set email alerts
|

The lost correlation between heat shock protein 70 (HSPA1A) and plasminogen activator inhibitor-1 in patients with type 2 diabetes and albuminuria

Abstract: We aimed to study the relation between plasma levels of stress-induced heat shock protein 70 (HSPA1A) with plasminogen activator inhibitor-1 (PAI-1) and highdensity lipoprotein cholesterol (HDL-C), apolipoprotein A1 (Apo-A1), and HDL-C/Apo-A1 ratio. In a matched case-control study on patients with diabetes (40 patients with albuminuria and 40 without albuminuria matched for age, sex, and body mass index), we observed that plasma levels of HSPA1A and PAI-1 are increased in patients with albuminuria (0.55±0.02 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(30 reference statements)
0
4
0
1
Order By: Relevance
“…The chaotic behavior that we mentioned for the inflammatory response can have some steady states also, such as health, sustained inflammation with or without the presence of sustained trigger [27] which is also in accordance to our subject. In our studies, in health we observe some physiologic correlations such as leptin and CRP, but in diseases with sustained inflammation such as RA or diabetes mellitus, we observe loss of some physiologic and emergence of pathologic correlations [14, 15, 16, 17]. One other important aspect of chaotic behavior is the possibility that the inflammation can be controlled by intervening at certain points, especially in the early course of the disease [28].…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The chaotic behavior that we mentioned for the inflammatory response can have some steady states also, such as health, sustained inflammation with or without the presence of sustained trigger [27] which is also in accordance to our subject. In our studies, in health we observe some physiologic correlations such as leptin and CRP, but in diseases with sustained inflammation such as RA or diabetes mellitus, we observe loss of some physiologic and emergence of pathologic correlations [14, 15, 16, 17]. One other important aspect of chaotic behavior is the possibility that the inflammation can be controlled by intervening at certain points, especially in the early course of the disease [28].…”
Section: Discussionmentioning
confidence: 61%
“…We previously showed the impact of inflammation on altering the physiological and pathological correlations [14, 15, 16, 17]. It is previously shown that leptin and CRP are correlated in healthy individuals [15, 18], and we reported the lost correlation between CRP and leptin in type 2 diabetes mellitus [15].…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Unfortunately, the existing study does not elucidate the clear mechanism for the changes, as it involves various biochemical reactions in the body. However, interestingly, this may be also associated with the synergistic effect of TCM and RP-GABA on antioxidant capacity in beef cattle (Azad et al, 2010;Nargesi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Adicionalmente, a HspA1A também já foi relatada na inibição da agregação da amilina ou IAPP, associada a diabetes melito tipo 2, reduzindo a resistência à insulina e melhorando os parâmetros clínicos (NARGESI et al, 2016;ROSAS et al, 2016) e no aumento da degradação da proteína TAU, relatado em estudo provavelmente pelo Sistema Ubiquitina Proteassoma e/ou por autofagia, na Doença de Alzheimer (SHAO et al, 2021).…”
Section: Hspa1aunclassified